The Limits of Resilience and the Need for Resistance: Articulating the Role of Music Therapy With Young People Within a Shifting Trauma Paradigm - Scrine, Elly (Frontiers in Psychology, 2021)
A broad sociocultural perspective defines trauma as the result of an event, a series of events, or a set of circumstances that is experienced as physically or emotionally harmful or life threatening, with lasting impacts on an individual’s physical, social, emotional, or spiritual wellbeing. Contexts and practices that aim to be “trauma-informed” strive to attend to the complex impacts of trauma, integrating knowledge into policies and practices, and providing a sanctuary from harm. However, there is a body of critical and decolonial scholarship that challenges the ways in which “trauma-informed” practice prioritizes individualized interventions, reinscribes colonial power relations through its conceptualizations of safety, and obscures the role of systemic injustices. Within music therapy trauma scholarship, research has thus far pointed to the affordances of music in ameliorating symptoms of trauma, bypassing unavailable cognitive processes, and working from a strengths-based orientation. In critiquing the tendency of the dominant trauma paradigm to assign vulnerability and reinforce the individual’s responsibility to develop resilience through adversity, this conceptual analysis outlines potential alternatives within music therapy. Drawing on a case example from a research project with young people in school, I elucidate the ways in which music therapy can respond to power relations as they occur within and beyond “trauma-informed” spaces. I highlight two overarching potentials for music therapy within a shifting trauma paradigm: (1) as a site in which to reframe perceived risk by fostering young people’s resistance and building their political agency and (2) in challenging the assumption of “safe spaces” and instead moving toward practices of “structuring safety.”